Efektivitas Penggunaan Kahoot Terhadap Penguasaan Kosakata Siswa Kelas X SMK Kansai Pekanbaru : The Effectiveness of Using Kahoot on The Vocabulary Mastery of Grade X Students at SMK Kansai Pekanbaru - Pardede, Lidia; Rahayu, Nana; Yohani, Adisthi Martha (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
21st century learning requires students to have critical, creative, communicative, and collaborative thinking skills. In the process of learning Japanese at SMK Kansai Pekanbaru, problems were found in students' low vocabulary mastery due to conventional learning methods and lack of use of interactive media. This study aims to determine the effectiveness of using Kahoot media in improving vocabulary in SMK Kansai Pekanbaru students. This study is a quantitative study using the true-experimental method and the Pretest-Posttest Control Group Design. The population of this study were grade X students of SMK Kansai Pekanbaru. The research sample consisted of 38 students who were divided into experimental classes and control classes through random sampling techniques. The research instruments were pre-test & post-test and Kahoot media. The results showed that there was a significant increase in the experimental class with an average score of 60 to 87 after being given the treatment of using Kahoot media. While the control class only experienced a slight increase from 63.78 to 67.33. These findings indicate that the use of Kahoot media is effective in improving students' mastery of Japanese vocabulary and encouraging students' motivation and activeness during the learning process. Therefore, Kahoot media is recommended as an interactive alternative media in foreign language learning in schools.